Dampak Sosial Dan Keamanan Masyarakat Hiroshima Nagasaki Pasca Dijatuhkanya Bom Atom Tahun 1945 - Kusniawati Kusniawati; Dhianada Salsabila Lugo; Ida Susilowati (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
Before the atomic bomb was dropped in the city of Hiroshima and Nagasaki, social and security conditions in the two cities were fairly prosperous. Hiroshima is known as a military logistics base, communication center, important port, and gathering place for Japanese troops. While Nagasaki was one of the largest ports in South Japan as well as an important city during the war. The research method used is a qualitative method with data sourced from trusted journals, books, and internet sites and by identifying phenomena or events that occur. This study aims to determine the impact of the imposition of American atomic bombs in Hiroshima and Nagasaki, especially for the social and security conditions of the two people. Behind the negative side of the incident, there are also some positive impacts including the end of World War II. Hiroshima and Nagasaki also turned into advanced cities after the atomic bomb tragedy.